Evaluation of presence and concentration of ppv in rootstocks derived from prunus davidiana (carr.) Franch - Pavelková, Petra; Kiss, Tomáš; Nečas, Tomáš (Mendelova univerzita v Brně, 2019)
Evaluation of the presence and concentration of PPV (Plum pox virus) in selected rootstocks was carried out in 2016-2017. For the purpose of the experiment we used rootstocks derived from crossbreeding of Prunus davidiana (Carr.) Franch, such as Cadaman and Barrier, and also a P. davidiana seedling. Peach seedling rootstock GF-305 was used as a control. The rootstocks were inoculated artificially with PPV strain M (Marcus). Both the rootstock and the inoculum were tested for presence of the virus by a serological method - semiquantitative DAS-ELISA test and molecular methods - RT-PCR, real-time RT-PCR and RT-LAMP. During the growing season the plants were evaluated for symptom intensity by using a scoring scale. The results show interdependency between symptom intensity and the amount of PPV in leaves, with DAS-ELISA test giving less positive samples than RT-PCR. The RT-LAMP and real-time RT-PCR methods were capable of revealing low concentrations of the virus even in symptom-free plants. The lowest PPV concentrations of all the four rootstocks were detected by real-time RT-PCR in P. davidiana. The highest PPV concentrations were detected in Barrier rootstock. In inocula, the lowest concentration was found in the inocula on Cadaman rootstock, whereas the highest PPV concentration was detected in the inocula inoculated on Barrier rootstock.
Keywords: DAS-ELISA; David's peach; Real-time RT-PCR; RT-LAMP; RT-PCR; Sharka; Stone fruit; Symptoms